2003
DOI: 10.1039/b303618a
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of transition and main group metal complexes supported by hydrogen-bonded zwitterionic polyphenolic ligandsElectronic supplementary information (ESI) available: full synthetic and spectroscopic details. See http://www.rsc.org/suppdata/cc/b3/b303618a/

Abstract: Reaction of Zr(O(i)Pr)4 or Sn[N(SiMe3)2]2 with the tris-phenol amine ligand H3L(Me/Me) results in the formation of zirconium or tin complexes containing the new C3-symmetric zwitterionic ammonium-trisphenolate ligand HL2-, while increasing the steric bulk of the ligand results in the isolation of a zirconium complex containing the known trianionic ligand L3-.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…The Zr-O and Zr-N bond distances fall in line with literature examples at an average of 2.021(3) Å and 2.398(3) Å, respectively [37][38][39][40]. Bischelated Zr complexes, similar to 7, have previously been reported with amine bis and tris(phenolate) ligands, which feature relatively small steric bulk on the phenolate groups or on the Zr precursor [6,37,41,42]. Various bischelated Zr complexes have been reported in the literature, but to the best of our knowledge 7 is the first example of a bis(ABP) Zr complex, where the potentially coordinating ligand pendant arm remains unbound [37,39,40,42].…”
Section: Synthesis Of Ti and Zr Clusterssupporting
confidence: 85%
“…The Zr-O and Zr-N bond distances fall in line with literature examples at an average of 2.021(3) Å and 2.398(3) Å, respectively [37][38][39][40]. Bischelated Zr complexes, similar to 7, have previously been reported with amine bis and tris(phenolate) ligands, which feature relatively small steric bulk on the phenolate groups or on the Zr precursor [6,37,41,42]. Various bischelated Zr complexes have been reported in the literature, but to the best of our knowledge 7 is the first example of a bis(ABP) Zr complex, where the potentially coordinating ligand pendant arm remains unbound [37,39,40,42].…”
Section: Synthesis Of Ti and Zr Clusterssupporting
confidence: 85%
“…1). 3 Upon inspection, the structure of 1-Cl reveals a titanium(IV) center disposed within a C 3 symmetric Nanchored tris-arylphenoxide scaffold. The Ti-O distances are similar ($1.80 Å ) and the Ti center lies in a trigonal bipyramidal environment with the N and Cl occupying the axial positions and with all Ad groups syn with respect to the Cl À group.…”
mentioning
confidence: 99%
“…However, several examples of mononuclear systems supported by non-encumbering N-anchored tris-arylphenoxide ligands have been scarcely reported, thus hinting that electronic factors might also play a role in formation of mono versus polynuclear compounds [6]. Recent reports by Kol [2] Brown [4] and others [3,5,6] have demonstrated that the (O 3 N) 3À framework is highly compatible with Ti(IV), and depending on the steric nature of the tripodal ligand, these systems can have considerable resistance to hydrolysis. Given the high Ti-O bond enthalpy ($673 kJ/mol) [7] and stability of the N-anchored tris-arylphenoxide core, we decided to investigate the chemistry of Ti(IV) complexes supported with the sterically demanding ligand (O 3 N) 3À (O 3 N 3À = tris(2-O,3-Ad,5-tBubenzyl)amine, Ad = 1-adamantyl, Scheme 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations